The Effect of Democratic Leadership Style on the Performance of Employees at PT. Medan Industry Area (Persero) - Andrysyah Andrysyah; Amin Basri; Junaida Junaida; Sudian Efendi; Nurhalimah Tambunan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The objective of this research were to determine the effect of democratic leadership style on performance of employees at PT. Medan Industry Area (Persero). The purpose of this research was to determine how the influence of democratic leadership style on performance of employees at PT. Medan Industry Area (Persero) ". Sources of data in this research are employees of PT. Medan Industry Area (Persero), with a population and a sample of 40 people (Respondents). The data was collected using a questionnaire and dating analysis using the SPSS 25 application. And the data collected using a questionnaire will then be tested for validity, reliability test, f test, and test the coefficient of determination. The results of this research indicate that the determination coefficient test (R2) in table 4:23 shows that the magnitude of the influence of the democratic leadership style is 0.069, this means that the democratic leadership style has an influence on employee performance. Thus it can be concluded that this indicates that the democratic leadership style is very good. And in the F test table 4.22 below, the value of Fcount > Ftable, the value of Fcount can be seen at the percentage point of the f test. Then the independent variable (X) (independent), namely leadership style (3.908> 4.09), has a significant effect on employee performance (dependent). Thus it can be concluded that with the influence of democratic leadership styles on employee performance, employees will be increasingly motivated to be able to provide good and maximum work results, and will direct all their abilities to improve performance, so they will be able to complete their tasks properly. And with the resulting Adjusted R Square value of 6.9% the effect and the rest is influenced by other variables.